Musicians in Transit Argentina and the Globalization of Popular Music - Karush, Matthew B. (Duke University Press, 2016)
In Musicians in Transit Matthew B. Karush examines the transnational careers of seven of the most influential Argentine musicians of the twentieth century: Afro-Argentine swing guitarist Oscar Alemán, jazz saxophonist Gato Barbieri, composer Lalo Schifrin, tango innovator Astor Piazzolla, balada singer Sandro, folksinger Mercedes Sosa, and rock musician Gustavo Santaolalla. As active participants in the globalized music business, these artists interacted with musicians and audiences in the United States, Europe, and Latin America and contended with genre distinctions, marketing conventions, and ethnic stereotypes. By responding creatively to these constraints, they made innovative music that provided Argentines with new ways of understanding their nation's place in the world.